Implementation of Education Based on Religious Moderation - Moh Wardi; Nur Atika Alias; Tawvicky Hidayat; Ali Usman Hali (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study discusses the implementation of religious moderation-based education which is described in two research focuses, namely first the forms and values of religious moderation-based education that have been implemented at SMPK Santo Yusup and secondly to find out the contribution of education based on religious moderation at SMPK Santo Yusup itself. This study uses a field qualitative approach. The data collection techniques in this study are using interviews, observation, and documentation. From this method, researchers process and analyze it to obtain data and information. The subjects in this study were school principals, 2 Catholic teachers, 2 Muslim teachers, and 3 students from different religions. The results of the study show that: first, the forms and values of education based on religious moderation at SMPK Santo Yusup are formed in the Faith Development activities and the inculcation of national values through PPKN learning. The two contributions to education based on religious moderation instill an attitude of openness, tolerance, anti-violence, an attitude of justice, and mutual respect for one another.